Investigation of Balanced Scorecard Measurement Method for Academicians Knowledge in Universities - Zainab, Amin; Awanis, Romli (American Scientific Publisher, 2018)
The tacit knowledge of workers represents one of the main competitive advantages resources in the organizations. The management of tacit knowledge resources is difficult due to intangibility nature of these resources. The evaluation of workers knowledge is important to enhance the business operations in the organizations based on the performance and value of knowledge resources. One of the main knowledge evaluation approaches is the balanced score, which aims to evaluate the workers knowledge based on the knowledge performance level (knowledge quantity and quality), and knowledge value (financial revenue). The main objective of this research is to investigate the importance of adopt effective key performance indicators to evaluate worker knowledge levels based on balanced score method. The academicians in universities represent the scope of this research. To address the research objective, a questionnaire survey was conducted with 35 academic staff from three universities in Iraq. In order to address the main objective of this research, the frequency, descriptive, and correlation analyses were conducted to address the research objective and test the research hypotheses. The significant results of the collected data show that the is a lack in evaluate the academicians’ knowledge in universities using effective methods. The evaluation of academicians’ tacit knowledge is very important to manage the knowledge resources in universities. The knowledge evaluation based on balanced score indicators considered as useful method to evaluate the academicians’ knowledge effectively based on the quantity, quality, and financial indicators. The contribution of this research is represented by the suggestion of balance score method to enhance the tacit knowledge evaluation in the university.